新加坡中学生中英双语近义词辨析能力及通过翻译习得中文近义词有效性的研究 = An investigation of Singaporean secondary school students’ competence in discrimination of near-synonyms in Chinese and English and the effect of translation in the learning of Chinese near-synonyms - 闫婧超 Yan, Jing Chao (Nanyang Technological University, 2020)
新加坡一直以来推行双语政策为国家培养精通双语的人才。然而，年轻一代的新加坡华人倾向在日常生活中使用英语交流，使得他们对华语的掌握程度日渐下降。而近义词一直以来都是词汇学习中的一大难点，在这样的多语言社会的影响下，新加坡中学生在中英近义词辨析方面会有什么样的表现？在这样社会语言环境下，华语教学也面临着挑战，加上现有的教材中对于近义词这一复杂的课题并没有提供太多的关注，因此通过了解新加坡中学生近义词习得状况以及在双语环境对近义词学习的影响，可以进一步的思考及探讨什么样的方法有助于新加坡中学生学习近义词。 本研究通过对30名本地中学生进行问卷调查和测试，从而探讨新加坡中学生在中英近义词上辨析上的情况，同时探讨翻译辅助中文近义词教学的可能性。研究结果显示语境的存在有助于中学生推测词义并进行近义词辨析，但同时也可能使学生过于关注两个词之间的共同点，造成误判的现象。此外，研究发现通过翻译有助于学生意识到两个中文近义词之间有差别，但是却无法辅助学生意识到具体差距是什么。事实上，这一部分学生们的作答很大程度上依赖了他们已有的英文近义词知识。本研究希望通过这项调查能加强对现今的近义词辨析教学状况的了解，并为未来制定近义词教学方式带来启发。 Singapore’s bilingual policy has been nurturing bilingual talents for the country. In recent years, younger Singaporean Chinese have developed a tendency to use English in their daily life, causing them to have a weaker command of Chinese. Near-synonyms, however, have always been a major difficulty in vocabulary learning. In this multilingual society, how will Singapore secondary school students perform when they are asked to differentiate Chinese and English near-synonyms? Also, Chinese language teaching has become more challenging in this multilingual society, and yet there are no existing teaching materials with a focus on the topic of near-synonyms. Therefore, by understanding the situation of synonym acquisition by Singapore secondary school students, as well as the influence of bilingual environment on synonym learning, we can explore the ways to aid Singapore secondary school students in near-synonyms learning. In this study, 30 secondary school students were recruited to take a synonym test and complete a questionnaire designed for this study. The aims of the study are to explore how secondary school students perform when differentiating Chinese and English near-synonyms and whether it would be possible for learners to use translation as an aid in the learning of near-synonyms in Chinese. The results of the study revealed that the presence of context allowed the students to infer the meanings of the words they did not know, and helped them in discriminating the synonyms. However, the presence of contexts might also cause confusion to the students when differentiating the near-synonyms. In addition, the results proved that translation did help the students see the difference between two Chinese near-synonyms. However, it did not assist the students to identify where the specific differences were, instead, it was found that the students relied more on their knowledge of the English near-synonyms. The results of this study can help teachers to understand the current situation in near-synonyms learning, and assist them in finding suitable strategies to facilitate the teaching of near-synonyms.